Osteology-based phylogeny and systematics implications of the genus Asio (Strigiformes, Strigidae) - Posso, Sérgio Roberto; Salomão, Camila Cardoso (Zootaxa, 2025)
We present the first phylogenetic analysis of Asio based on an osteological dataset comprising 35 characters (cranial and postcranial) from 36 specimens representing seven species. Parsimony analysis resulted in a single tree (50 steps, CI = 0.72, RI = 0.75): ((Asio otus ((Asio stygius (Asio clamator/Asio grammicus))) ((Asio solomonensis ((Asio capensis/Asio flammeus))))). This topology supports the previously proposed synonymization of Pseudoscops and Nesasio into Asio, based on molecular phylogenetic studies. The primary discrepancy between morphological and molecular datasets lies in the relationships among A. otus, A. grammicus, and A. clamator. Our results provide support (Bootstrap = 100, Bremer = 12, and 17 synapomorphies) for a sister relationship between A. grammicus and A. clamator. Conversely, molecular phylogenies suggest a closer relationship between A. clamator and A. otus. Additionally, we present the first phylogenetic placement of A. stygius, which our analysis identifies as most closely related to the A. grammicus/A. clamator clade (Bootstrap = 56, Bremer = 6, and eight synapomorphies). This finding aligns with the shared Neotropical distribution and we suggest A. grammicus likely evolved from an isolated ancient lineage shared with A. clamator. Significantly, the observed intraspecific osteological variation highlights the necessity for further taxonomic investigations to elucidate species diversity within Asio, particularly within the A. flammeus and A. clamator complexes.